A Firm Approach to National Competitiveness: The Role of Multinational Firms in Country’s Global Competitiveness - Inga A. MEZINOVA; Janetta B. AMIRKHANYAN; Oleg V. BODIAGIN; Milena M. BALANOVA (Communications of International Proceedings, 2021)
Recent years have seen growing recognition that multinational firms are resourceful actors that can play a crucial role for economic development and social change. However, while these roles are widely recognized, relevant theories and debates have often remained unconnected. This part of a wider research aspires to contribute to better understanding of the role of multinational firms for national competitiveness through exploration of the empirical intersections around the global operations of multinational firms (transnationality index) and global country competitiveness (within the methodology used by the World Economic Forum for Global Competitiveness Index until 2018).
Keywords: National Competitiveness; Global Competitiveness; Multinational Firm; Transnationality Index.